2010
DOI: 10.1002/pssb.201000205
|View full text |Cite
|
Sign up to set email alerts
|

Separation of metallic single‐walled carbon nanotubes using various amines

Abstract: Separation of metallic single-walled carbon nanotubes (m-SWNTs) using various amines in different concentrations was investigated. The SWNTs dispersions were characterized with Vis-NIR and Raman spectrometers. The proportion of m-SWNTs toward semiconducting SWNTs increased with an increase of concentration of amines. SWNTs thin films were prepared from the SWNTs dispersion. The sheet resistance of SWNTs films decreased with an increase of proportion of m-SWNTs. We have already reported the effective dispersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…For example, with unfunctionalized gold probe (Figure a), there is little difference in the mean adhesion force (mean +/‐ one standard deviation) between the S (26.7 ± 3.1 nN) and M (28.0 ± 3.8 nN) nanotubes, indicating that gold does not exhibit preferential selectivity for metallic or semiconducting SWNTs. The force histograms measured with the three functionalities (Figure b–d) differ significantly from those of the non‐functionalized probe, corroborating that some of these functionalities have SWNT metallicity selectivity, confirming determinations by others made using indirect methods …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…For example, with unfunctionalized gold probe (Figure a), there is little difference in the mean adhesion force (mean +/‐ one standard deviation) between the S (26.7 ± 3.1 nN) and M (28.0 ± 3.8 nN) nanotubes, indicating that gold does not exhibit preferential selectivity for metallic or semiconducting SWNTs. The force histograms measured with the three functionalities (Figure b–d) differ significantly from those of the non‐functionalized probe, corroborating that some of these functionalities have SWNT metallicity selectivity, confirming determinations by others made using indirect methods …”
Section: Resultssupporting
confidence: 80%
“…Various functional groups, specifically amine, naphthalene and pyrene (Figure b) were used for tip functionalization in demonstration of this direct force measurement technique. These functional groups have been found (theoretically or experimentally in the presence of other molecules such as surfactants and solvents) to have metallicity‐dependent SWNT selectivity …”
Section: Peak Force Qnm Adhesion Force Spectroscopy Detailsmentioning
confidence: 99%
“…In this first stage, the high reactivity of primary amines with spheroidal fullerenes renders their cages hydrophilic for removal. (It is interesting to note that functionalized amines were used to separate metallic from semiconducting nanotubes. ) Our second stage requires only one column for C 90 , C 96 , and C 100 fullertube isolation. HPLC purification is rapid, cost-effective, facile, and green (i.e., less solvent, less money, less time, and less chemical waste).…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies employing aminated dispersing agents to exfoliate carbon nanotubes have demonstrated increased affinity of amine groups for metallic carbon nanotubes. 23,24 Similar interactions with zero bandgap graphene nanoplatelets could explain the increased affinity of Tetronics. Interestingly, Tetronic 304, which is the smallest molecular weight copolymer tested, displayed dispersion efficiencies comparable to much higher molecular weight copolymers such as Pluronic F88 and Tetronic 908.…”
mentioning
confidence: 97%